Appropriate bleaching technique for coconut fiber. Issue 3 (3rd April 2019) - Basu, Gautam; Mishra, Leena; Samanta, Ashis Kumar
ABSTRACT: Recipes for bleaching of coconut fiber at both ambient and elevated temperature were investigated using appropriate statistical design of experiments using hydrogen peroxide with essential bleaching assisting auxiliaries. The statistical tool is also being utilized to suggest optimized recipe for the treatments considering mainly whiteness index, yellowness index, and tenacity. Statistical computation affirmed need of higher amount of bleaching chemicals in elevated temperature than ambient bleaching. Both the bleaching treatments were resulting in small mass loss essentially of noncellulosic nature including lignin and thus result in improved mechanical properties. The change in whiteness and yellowness index of the bleached fiber under the shed storage condition for duration of 2 years was found to be negligible.